JAK Inhibitors and Oxidative Stress Control - Charras, Amandine; Arvaniti, Pinelopi; Le Dantec, Christelle; Dalekos, George N.; Zachou, Kaliopi; Bordron, Anne; Renaudineau, Yves (Frontiers in Immunology, 2019)
Primary Sjӧgren’s Syndrome (SjS) is a complex autoimmune epithelitis, with few treatment options, but the use of Janus kinase (JAK) inhibitors is promising since suppression of the JAK/signal transducer and activator of transcription (STAT) pathway improves sicca manifestations. Playing a primary and pathogenic role in disease development, the oxidative stress response is upregulated in activated salivary gland epithelial cells (SGECs) from patients with SjS. Therefore, the aim of this study was to investigate whether JAK inhibitors would suppress SGECs activation in response to an oxidative stress. For this purpose the human salivary gland (HSG) cell line was used and cells were treated with the reactive oxygen species (ROS) inducer hydrogen peroxide (H2O2) or with interferons (IFN Type I and Type II), used as positive controls, to mimic activated SGECs as observed in SjS patients. Afterwards the levels of the intracellular adhesion molecule-1 (ICAM-1) and the regulatory programmed-death ligand-1 (PD-L1), were measured by real time PCR and flow cytometry, and the STAT1/3 phosphorylation status was assessed by Western blotting. Using the HSG cell line, our results showed that both ICAM-1 and PD-L1 are induced by ROS through pSTAT3, and that this activation pathway is reversed by the use of JAK inhibitors, AG490 and ruxolitinib, as well as by N-acetylcysteine which is a direct inhibitor of ROS. These findings open new perspectives regarding the pathogenesis and therapeutic possibilities for SjS.